Strategic Management Roadmap: Formulation, Implementation, and Evaluation to Develop Islamic Higher Education Institution - Junaidah, Junaidah; Basyar, Syarifudin; Pahrudin, Agus; Fauzan, Ahmad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
This study aimed to formulate a model for the development, implementation, and evaluation of strategic management systems in Islamic higher education institutions to achieve the goals they have set in a competitive and dynamic environment. The researchers conducted this study at Universitas Islam Negeri (UIN) Raden Intan Lampung for nine months, from January to September 2020. This study employed the qualitative paradigm of phenomenology. The strategy to realize excellence is known as the university strategies. The strategies consist of ten aspects: 1) increasing the quality of inputs, 2) increasing superior learning processes and outcomes based on the competency and expertise areas, 3) increasing research and research-based service by emphasizing the significance of the results, 4) improving the quality of human resources, 5) improving students’ achievement academically and non-academically, 6) increasing financial independence, environmentally sound assets, land, and infrastructure, 7) increasing accreditation rankings, 8) mainstreaming information technology as the backbone of credible, accountable, transparent, responsible and just governance, 9) improving cooperation, and 10) improving collaboration with other institutions and universities. This research can be a reference for universities' policy-makers in revising the universities' management.